Arginine Silicate Inositol Complex Accelerates Cutaneous Wound Healing - Durmus, Ali Said; Tuzcu, Mehmet; Ozdemir, Oguzhan; Orhan, Cemal; Şahin, Nurhan; Ozercan, Ibrahim Hanifi; Şahin, Kazım (Humana Press Inc, 2017)
Arginine silicate inositol (ASI) complex is a composition of arginine, silicon, and inositol that has been shown to have beneficial effects on vascular health. This study reports the effects of an ASI ointment on wound healing in rats. A full-thickness excision wound was created by using a disposable 5 mm diameter skin punch biopsy tool. In this placebo-controlled study, the treatment group's wound areas were covered by 4 or 10 % ASI ointments twice a day for 5, 10, or 15 days. The rats were sacrificed either 5, 10, or 15 days after the wounds were created, and biopsy samples were taken for biochemical and histopathological analysis. Granulation tissue appeared significantly faster in the ASI-treated groups than in the control groups (P < 0.05). The mean unhealed wound area was significantly smaller, and the mean percentage of total wound healing was significantly higher in ASI-treated wounds than in the control wounds. Hydroxyproline, collagen, and matrix metalloproteinases were measured in the granulated tissue and found to be affected. Inducible nitric oxide synthase (iNOS), endothelial nitric oxide synthase (eNOS), collagen, matrix metalloproteinase-2 (MMP-2), matrix metalloproteinase-9 (MMP-9), vascular endothelial growth factor (VEGF), fibroblast growth factor (FGF), epidermal growth factor (EGF), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kappa B), and various cytokines (TNF-alpha and IL-1 beta) measured in this study showed a significant fall in expression level in ASI-treated wounds. The results suggest that topical application of ASI ointment (especially 4 % concentration) has beneficial effects on the healing response of an excisional wound.
Keywords: Arginine silicate inositol; Wound healing; Molecular mechanism